Niche design theory as a tool for media memory research - D. S. Artamonov; S. V. Tikhonova; E. E. Chebotareva (Шаги, 2022)
The article discusses the methodological possibilities of niche construction theory in the context of media memory study. The authors consider media memory as a mechanism for the production, storage and oblivion of collectively shared ideas about the Past in a digital environment that has integrated all human culture into the media space. The theory of niche construction makes it possible to explain the processes of formation of collective memory and to show its correlation with individual memory, extrapolating the methodology of biological science to the humanities. The authors analyze the main ideas of Richard Heersmink concerning the role of the ecology of memory and distributed identities in the construction of narrative niches. Individuals inherit narrative niches and modify them as a result of individual as well as collective creativity in reproducing ideas about the Past. The methods of media content production, the types of individual behavior in social networks and the features of its interaction with information technologies determine the logic of constructing memory niches in the digital environment. The authors conclude that digital intermediaries in the form of technologies and social media have a significant impact on the construction of individual and public narrative niches, providing the possibility of their transition into one another.